Computational thinking in the Ethiopian secondary school ICT curriculum. Issue 4 (2nd October 2022) - Kassa, Ermias Abebe; Mekonnen, Enguday Ademe
ABSTRACT: Background and Context: Computational thinking (CT) is one of the 21st century skills required of graduates joining the workforce. Hence, countries have begun to incorporate CT into their curricula. Objective: There is, however, a dearth of research coming from Africa showing the extent of CT's integration in the science, technology, engineering, and mathematics (STEM) curriculum. The main objective of this study was to assess the extent to which CT was integrated into Ethiopia's secondary school (Grades 9–12) information and communication technology (ICT) curriculum. Method: The Ethiopian secondary school (ESS) ICT curriculum, as portrayed in the syllabi, textbooks, and teaching guides, served as the data source for the study. The data were then subjected to qualitative thematic analysis in the Atlas.ti environment. Findings: Despite the emphasis on ICT literacy, the analysis revealed that CT was incorporated into the curriculum through the use of Logo, Excel, and multimedia projects. The integration could not however be described as "systematic". Implications: The research could provide practitioners and policymakers with evidence to chart a path for the planned integration of CT into the ESS ICT curriculum. Similar studies from K-12 to higher education levels could also benefit from the research.